Reaching young adult smokers through the Internet: Comparison of three recruitment mechanisms - Ramo, Danielle E. (Oxford University Press, 2010)
INTRODUCTION: While young adults have the highest prevalence of cigarette smoking of any adult age group, studies of tobacco and other substance use have reported challenges in recruiting this age group. The Internet may be a useful tool for reaching young adult smokers. The present study compared three Internet-based recruitment methods for young adult smokers to complete a survey about tobacco and other substance use: Craigslist advertisements, other Internet advertisements, and E-mail invitations through a survey sampling service. METHODS: Recruitment campaigns invited young adults aged 18–25 years who had smoked at least one cigarette in the past 30 days to complete an online survey. Recruitment methods were compared across recruitment numbers, costeffectiveness, and demographic and smoking characteristics of recruited participants. RESULTS: In 6 months, 920 people gave online consent to determine eligibility to complete the survey, of which 336 (36.5%) were eligible, and 201 (59.8%) completed the survey. While Internet advertisements yielded the largest proportion of recruited participants and completed surveys overall, Craigslist and sampling strategies were more successful at targeting young adult smokers who went on to complete the survey and were more costeffective. Participants differed in demographic and substance use characteristics across the three recruitment mechanisms. DISCUSSION: We identified success at reaching young adults who have smoked cigarettes recently through the Internet, though costs, participant eligibility, proportion of completed surveys, and respondent characteristics differed among the three methods. A multipronged approach to Internet recruitment is most likely to generate a broad diverse sample of young adult smokers.